A state-of-the-art review on particulate wood polymer composites: Processing, properties and applications. (September 2020) - Khan, Mohammad Z.R.; Srivastava, Sunil Kumar; Gupta, M.K.
Abstract: In the present decade, the demands for recyclable, environmentally friendly and low-cost with good strength composites materials have been significantly increased. In this context, the particulate wood polymer composites have attracted the researchers owing to their eco-friendliness, low-cost as they are prepared using waste wood particles, and good mechanical and physical properties. These composites were prepared by filling the waste wood particles into the polymers using different fabrication methods such as extrusion, hand layup, compression moulding, injection moulding and additive manufacturing (3D printing). A good number of research works have been reported on the testing and characterization of wood composites for the various applications so far. This fact motivated to prepare a state-of-the-art review on the recent developments in processing, characterization, and applications of wood composites. This paper presents a discussion on the chemical structure and properties of different types of wood species. The mechanical, thermal and water absorption behaviour of thermosets, thermoplastics and biopolymers based wood composites have also been discussed. Further, characterization of the nano biocomposites prepared using nanocellulose/nanoparticles of wood are also presented. The outcomes of the present review provide a good understanding of wood composites that will encourage the researchers for further research works & developments of novel wood composites for the advanced applications. Highlights: Wood composites are environmental friendly and low cost materials. Study on fabrication methods of wood composites. Characterization of wood composites. Characterization of chemically treated wood composites. Recent applications of wood composites.